SPECIES DIVERSITY AND ECOLOGICAL FEATURES OF DIATOM ASSEMBLAGES FROM THE SURFACE LAYER OF THE WESTERN ANTARCTIC BOTTOM DEPOSITS (THE ARGENTINEAN ISLANDS) - Ogienko, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
This paper is devoted to diatom taxonomic diversity in marine surface deposits of the Argentinean Islands water area near the "Academician Vernadsky" Ukrainian Antarctic Station. The research is aimed at analyzing the palaeofacial conditions of diatom assemblage formation and various agents which affected their taxonomic composition and ecological structure. To study the fossil diatom assemblages, the material was treated in accordance with standard techniques. Diatom frustules were examined by light and scanning electron microscopy. Quantitative estimation showed up to 600–800 diatom frustules in each slide. The share has been identified for each species in the assemblage. The research yielded data on the taxonomy and ecological features of the diatom assemblages. There have been analyzed the major factors in the assemblage formation. The species composition of the assemblage suggests that the surface layer (0–3 cm) of the Argentinean Islands deposits was being formed in a hydrological environment similar to the present one. Lack of benthos can be accounted for by a sea depth of over 150 m below the photic zone. The predominant planktonic littoral cold-water species, cryophile diatom species and scarce oceanic warm-water ones must have occurred in the near shore waters with ice cover, which, due to cold winters, remained thick for 7–8 months per year. The results suggest that the temperature of the marine surface waters ranged from –1,5 °C to +3 °C during the vegetation season. With average summer temperatures of +0,5 … +1,5°C, ice remained drifting in the waters throughout the summer. The distribution of planktonic diatom species in the surface bottom assemblages coincides with their modern areas, which is accounted for by weak sea surface currents and low hydrologic dynamics. It can be assumed that the oceanic subantarctic diatoms were brought into shallow Antarctic coastal waters by tides. Due to their sensitivity to changes in environmental variables, diatoms are widely used as an indicator in reconstructions of palaeoclimatic variations and fluctuations resulting from global warming, as well as in the geological and paleoceanological investigations of the South Ocean. However, fossil siliceous microalgae in the North-Western Antarctic bottom deposits had not been given a detailed description, which necessitated a thorough analysis of diatoms from the sediments in the Argentinean Islands water area. Our scientific research into the diatom flora development has enhanced the understanding of the Quaternary Antarctic palaeoclimate variables. The new diatom data may be of use to those undertaking paleoceanological and sedimentological inquiry.